Genetic generalized epilepsies with frontal lesions mimicking migratory disorders on the epilepsy monitoring unit. Issue 2 (12th March 2020) - Fauser, Susanne; Cloppenborg, Thomas; Polster, Tilman; Specht, Ulrich; Woermann, Friedrich G.; Bien, Christian G.
Abstract: Objective: Some patients with genetic generalized epilepsy (GGE) may present with ambiguous and atypical findings and even focal brain abnormalities. Correct diagnosis may therefore be difficult. Methods: We retrospectively collected six patients investigated on the epilepsy monitoring unit with MRI abnormalities mimicking focal cortical dysplasia (FCD‐like) or heterotopias, but with semiology and EEG features of GGE. We compared them to four additional patients with GGE and nonmigratory abnormalities. Results: All six patients presented with frontal MRI lesions: radial ("transmantle, " n = 4), cortical‐subcortical (n = 1), and periventricular heterotopia (n = 1). Five had positive family histories. Semiologic lateralizing signs compatible with the lesion were seen in four. Five patients had 3/s spike‐wave complexes, with an asymmetric appearance in three. Regional EEG changes matched with the side of the abnormality in three patients. Invasive EEG (n = 2) or postoperative outcomes (n = 3) argued against an ictogenic role of the MRI abnormalities. Histology showed mild malformation of cortical development, but no focal cortical dysplasia. The six patients were finally diagnosed with juvenile myoclonic epilepsy (n = 2), juvenile absence epilepsy (n = 2), or GGE not further specified (nfs, n = 2). Compared to these patients, the other four (final diagnoses: childhood absence epilepsy, n = 1; perioral myoclonia with absences, n = 1; and GGE nfs, n = 2) had no lateralizing EEG findings. Significance: Patients with GGE may have coincidental MRI abnormalities. These cases are challenging as frontal epilepsy and GGE can present with similar semiologies. GGE with coincidental FCD‐like lesions/heterotopias is in particular difficult to diagnose as patients have more lateralizing features (in semiology and EEG) than those with tumors. A detailed noninvasive presurgical evaluation may be justified. We point out red flags that may help to distinguish GGE from frontal epilepsy, even in the presence of brain abnormalities: 3/s spike waves (even if asymmetric), changing lateralizing signs at different times, and a positive family history hinting at GGE.